2021
DOI: 10.3390/ijerph182111539
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health of Australian Adults: Distribution and Time Trends of Dental Caries, Periodontal Disease and Tooth Loss

Abstract: This study was conducted to describe the distribution and trends in dental caries, periodontal disease and tooth loss in Australian adults based on the findings of the National Study of Adult Oral Health 2017–18. A cross-sectional study of a random sample of Australians aged 15+ years was carried out, employing a three-stage stratified probability sampling design. Data were collected via online survey/telephone interviews using a questionnaire to elicit self-reported information about oral health and related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
15
0
4
Order By: Relevance
“…Dental caries is a highly prevalent infectious bacterial disease, ranking first in prevalence among 328 diseases worldwide in 2016 (Vos et al, 2017). Dental caries can adversely impact the quality of life of affected patients, resulting in complications including pain and, in severe cases, tooth loss (Aldosari et al, 2021;Amarasena et al, 2021;Santos et al, 2021). Streptococcus mutans (S. mutans) is an essential cariogenic bacterium that metabolizes carbohydrates within the oral cavity and thereby lowers the local pH at the tooth surface (Loesche, 1986;OmerOglou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries is a highly prevalent infectious bacterial disease, ranking first in prevalence among 328 diseases worldwide in 2016 (Vos et al, 2017). Dental caries can adversely impact the quality of life of affected patients, resulting in complications including pain and, in severe cases, tooth loss (Aldosari et al, 2021;Amarasena et al, 2021;Santos et al, 2021). Streptococcus mutans (S. mutans) is an essential cariogenic bacterium that metabolizes carbohydrates within the oral cavity and thereby lowers the local pH at the tooth surface (Loesche, 1986;OmerOglou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Foundation work in South Australia was built to give a rich picture of child and adult dental health, as well as the dental health of Aboriginal and Torres Strait Islander peoples. The paper in this issue by Amarasena et al [45] describes a recent national oral health survey and the changes in dental health over the past 30 years.…”
Section: Oral Healthmentioning
confidence: 99%
“…According to the World Health Organization (WHO), 60-90 percent of persons have dental caries [11]. Research shows that obesity and dental caries are strongly linked [12]. Adults in the Kim et al, 2020 study were shown to have a link between being overweight or obese and having more advanced dental caries [13].…”
Section: Introductionmentioning
confidence: 99%